Seasonal and Spatial Variations in Fishing Intensity and Gearwise Landings of the Vembanad Lake - B., Madhusoodana Kurup; T.M., Sankaran; P., Rabindranath; M.J., Sebastian (Fishery Technology, 2025)
The variations noticed in the fishing intensity on an annual basis in the different regions of the Vembanad lake arc discussed. Stake nets and dip nets acconnted for 72.48% of the total landings; the former contributing to 53.14%. The contributions from gill nets, seines, cast nets, line fishing and other indigenous fishing methods are respectively 10.15, 9.68, 3.49, 2.54 and 1.66%. Stake and dip nets are almost confined to the northern sector (Cochin backwaters), contributing 57 and 20.7% respectively of the production. Seines and gill nets acconnted for 8.5 and 8.3% respectively in this sector. In the southern sector (Thannecrmukkom to Allcppey), the stationary gears are rarely noticed, the major part of the landings being obtained from gill nets (34.34%), seines (24.67%) and cast nets (19.04%).